THE DISPARITY IN JUDGES' DECISIONS ON THE CRIME OF SEXUAL VIOLENCE AGAINST CHILDREN IS REVIEWED FROM LAW NUMBER 35 OF 2014 CONCERNING AMENDMENTS TO LAW NO. 23 OF 2002 CONCERNING CHILD PROTECTION (Study of Decision Number 858/Pid.Sus/2022/PN Bjm and Number - Rengganis, Mutiara; Gagarin Akbar, Muhamad Gary; Arafat, Zarisnov (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2024)
Sexual violence against children is a serious violation of human rights and moral norms. This study focuses on the disparity in sentencing in two cases of sexual violence against children involving the biological father as the perpetrator, namely decision Number 858/Pid.Sus/2022/PN Bjm and Number 137/Pid.Sus/2023/PN Grt. Both are included in the category of familial abuse, where violence occurs in the family environment. Although both cases involve violations of Article 81 paragraph (3) of the Child Protection Law with a maximum penalty of 20 years in prison, there are differences in sentencing. In the first verdict, the perpetrator was sentenced to 18 years in prison and chemical castration for 2 years, while in the second verdict, the perpetrator was sentenced to 20 years in prison without chemical castration. This disparity is caused by differences in juridical and non-juridical considerations by judges, although both aim to achieve legal certainty and the prevention of future crimes.